English Language Needs for Receptionists in Raja Hotel Kuta Mandalika Lombok - Navirie Ahmad Fauzi; Muhammad Amin; Atri Dewi Aziz (Journal of English Education Forum (JEEF), 2026)
This study aims to identify and analyze the English language needs of receptionists at Raja Hotel Kuta Mandalika Lombok, one of Indonesia’s super-priority tourism destinations, where receptionists play a crucial role as the first and last point of contact for international guests. Using a mixed-method approach through questionnaires, observations, and semi-structured interviews with six receptionists and four front-office staff members, the study found that all English language skills listening and speaking are highly important, particularly for handling reservations, greeting guests, providing information, and managing complaints. Although receptionists generally demonstrate good English proficiency, especially in greeting, reservation handling, and telephone communication, weaknesses remain in explaining hotel facilities, delivering tourist information, and handling guest complaints empathetically. Key challenges include communication with guests who have limited English proficiency, such as Chinese and Korean visitors, and reliance on translation tools. Therefore, the study recommends regular micro-trainings, role-play simulations, bilingual service scripts, and collaboration between hotels and educational institutions to develop ESP-based English training programs tailored to real workplace needs.